2016
DOI: 10.1038/srep32238
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized (non)-regenerated cellulose affects fundamental cellular processes of wound healing

Abstract: In this study we investigated how hemostats such as oxidized regenerated cellulose (ORC, TABOTAMP) and oxidized non-regenerated cellulose (ONRC, RESORBA CELL) influence local cellular behavior and contraction of the extracellular matrix (ECM). Human stromal fibroblasts were inoculated in vitro with ORC and ONRC. Cell proliferation was assayed over time, and migration was evaluated by Live Cell imaging microscopy. Fibroblasts grown in collagen-gels were treated with ORC or ONRC, and ECM contraction was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…*p < 0.05 vs. control; **p < 0.05 vs. control and GELA; ***p < 0.05 vs. control, GELA and ORC. Two-way ANOVA with 2-stage step-up method of Benjamini, Krieger and Yekutieli was applied (q = 0.05, n = 5-7/experimental group) to the absence of buffer-acting serum components [26,27]. Consistent with previous findings, this study found that ONRC caused the strongest decline of pH values during degradation, as frayed and less condensed fibers form a larger surface area, leading to more rapid release of acidic groups [27].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…*p < 0.05 vs. control; **p < 0.05 vs. control and GELA; ***p < 0.05 vs. control, GELA and ORC. Two-way ANOVA with 2-stage step-up method of Benjamini, Krieger and Yekutieli was applied (q = 0.05, n = 5-7/experimental group) to the absence of buffer-acting serum components [26,27]. Consistent with previous findings, this study found that ONRC caused the strongest decline of pH values during degradation, as frayed and less condensed fibers form a larger surface area, leading to more rapid release of acidic groups [27].…”
Section: Discussionsupporting
confidence: 86%
“…Two-way ANOVA with 2-stage step-up method of Benjamini, Krieger and Yekutieli was applied (q = 0.05, n = 5-7/experimental group) to the absence of buffer-acting serum components [26,27]. Consistent with previous findings, this study found that ONRC caused the strongest decline of pH values during degradation, as frayed and less condensed fibers form a larger surface area, leading to more rapid release of acidic groups [27]. In contrast, GELA proved to be pH neutral and maintained prolonged structural integrity over 24 h. Our findings seem plausible, since reported time frames for complete degradation in vivo vary from 14 days up to 5 weeks for CBH, while the same process may take as long as 4-6 weeks for GBH and may be accelerated und standardized in in vitro conditions [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be attributed to the ORC fraction of the product Promogran. A drop in pH level was described for oxidized cellulose hemostatic agents, although some authors describe differences between investigated media types [ 40 , 41 ]. The shift to a more acidic value might on the one hand occur by degradation, as the depolymerization leads to the release of acidic groups [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the beneficial effect of these local hemostatic agents in preventing bleeding in dental surgery, available data comparing their effectiveness and efficiency is still scarce and inconclusive. Methodological heterogeneities, such as the lack of a standard therapy and comparable treatment regimens, are noticeable among studies, as well as the reduced number of randomized controlled trials [2,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Effectiveness Of Different Biosurgical Hemostatic Agents In mentioning
confidence: 99%